Pola sebaran dan preferensi habitat kodok buduk (Duttaphrynus melanostictus Schneider, 1799) di Kecamatan Tembalang, Semarang - Zuni Miftakhurrohmah; Karyadi Baskoro; Rully Rahadian (Jurnal Biologi Tropika, 2019)
Asian common toad is a human-commensal organism that can easily be found around. This species is the most common species that has a very wide habitat range, from backyard to secondary forest. Tembalang has relatively diverse habitat type which will be suitable for Asian common toad's habitat, but, as the land use of the area are changing from rural to urban land use, the toad population is changing as well. The objectives of the research are to understand the distribution pattern of Duttaphrynus melanostictus along with its habitat preference in Kecamatan Tembalang, Semarang. The research was taken in March – July 2019, by observing the toad population in three different types of habitat (developed habitat, vegetation-covered habitat, and open habitat). The data was taken using visual encounter survey method, at night starting from 7 to 10 p.m. The data of toad's prevalence was analyzed using Morisita index to comprehend the distribution pattern, while the habitat variable data was analyzed using Ward's Cluster analysis using PAST software. From the research, can be concluded that the Asian common toad is distributed with clumped pattern in Tembalang, with Morista index of 7.23, without any specific preference to habitat's type of substrate. The distribution pattern mostly influenced by the macro environmental condition, such as vegetation cover, elevation, buffer distance to nearest river (or water reservoir), and temperature.